Marketing children's party services : Rugged Earth Adventures - O'Brien, Justin ([London] : SAGE, 2016)
With increasing numbers of cash-rich but time-poor families, entrepreneurs have increasingly commercialised the children's party concept, offering a wide range of imaginative, outsourced propositions. Beginning by outlining the size and scope of this emergent industry, this case focuses on an outdoors adventure party service that uses a militaristic theme. Introducing a creative and fun but low barrier-to-entry business model, the case uses an entrepreneurial business venture to explore contextual marketing analysis.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Marketing -- Case studies; Amusements -- Marketing -- Case studies